GROUNDING OF USE OF MODERN APPLE VARIETIES FOR THE PRODUCTION OF FRUIT WINES AND FRESH CONSUMPTION BASED ON BIOCHEMICAL RESEARCH - Кузнецов, Андрій; Войцехівський, Володимир; Гладун, Андрій; Ткачук, Світлана; Токар, Анастасія; Сметанська, Ірина; Мулярчук, Оксана (SWorldJournal, 2022)
Complex of biochemical indicators modern late varieties of apples, which forming nutritional and biological value of fruits was analyzed. Calculated rating grade of the researching varieties. Florina, Champion, Radoghost, Scythian gold, Todes and Pearl of